Safety and immunogenicity of Ad26.COV2.S in adolescents: Phase 2 randomized clinical trial - Jelena Tica; Veronica V. Rezelj; Benoit Baron; Vitalija van Paassen; Javier Zaidman; Lee Fairlie; Gert Scheper; Mathieu Le Gars; Frank Struyf; Macaya Douoguih; Javier Ruiz-Guiñazú (Human Vaccines & Immunotherapeutics)
We conducted a randomized, Phase 2 trial to assess the safety and humoral immunogenicity of reduced doses/dose volume of the standard dose of Ad26.COV2.S COVID-19 vaccine (5 × 1010 viral particles [vp]) in healthy adolescents aged 12–17 years. Participants were randomly assigned to receive Ad26.COV2.S at reduced dose levels of 0.625 × 1010 (0.5 mL), 1.25 × 1010 (0.5 mL) or 2.5 × 1010 (0.5 mL or low volume 0.25 mL) vp in a 1- or 2-dose (56-day interval) primary schedule. Adolescents who received a 1-dose primary schedule received a 2.5 × 1010 vp booster dose 6 months later. Safety and humoral immunogenicity were assessed up to 6 months post-last vaccination. All regimens were well tolerated, with no safety concerns identified. Local and systemic solicited AEs in adolescents were consistent with the known safety profile in adults. All 1- and 2-dose Ad26.COV2.S primary schedules elicited robust peak Spike-binding antibody responses and virus neutralizing titers against the reference strain, in participants with and without preexisting SARS-CoV-2 immunity. Immune responses were durable for at least 6 months. Spike-binding antibody responses were comparable to those elicited in young adults aged 18–25 years who received a standard dose of Ad26.COV2.S in Phase 3 efficacy studies Reduced doses/dose volume of Ad26.COV2.S had an acceptable safety profile and elicited robust humoral immune responses in adolescents aged 12–17 years. All 1- and 2-dose schedules elicited Spike-binding antibody responses that were comparable to an adult population in whom efficacy has been demonstrated using a higher vaccine dose. (clinicaltrials.gov NCT05007080).